(untitled) (Kronika Bydgoska, 2012)
The chronicie presents the abundant operations of the TMMB Friends of Bydgoszcz Association in 2012. Noteworthy are first of all TMMB publications, e.g. ‘Bydgoszcz Calendar’ and ‘Bydgoszcz Chronicie’ for 2012, TMMB Monograph: ‘Faithful to their city’ with a supplement, the book ‘The Brda River and the Bydgoszcz Canal’ written by engineer K. Dudek and published in co-operation with the Polish Bridge Construc- tors’ Union Kuyavian-Pomeranian Branch, and volume 1 of ‘The Ency- clopaedia of Bydgoszcz’ featuring almost one thousand entries. The TMMB association participated in the organisation of the Bydgoszcz Year of Leon Wyczółkowski through preparation of, among others, the nationwide conference ‘Wyczółkowski differently’, Leona Wyczółkowskiego Street holiday combined with competitions and promotion of the book ‘L. Wyczółkowskiego Street in Bydgoszcz Skrzetusko’, and concerts of the band ‘Paderewski Kwartet’. Other events worth mentioning include: ‘Marian Concerts with a Rosę’ at the Bydgoszcz cathedral, numerous plaąues commemorating for example J.D. Salinger, intemational conference ‘Bridges-Tradition-Modernity’ (coorganisation), competition ‘Bydgoszcz with flowers and greenery’, regional education competitions for young people combined with getting Young Friend of Bydgoszcz badges, old cemeteries fundraiser, advocacy of the metropolitan aspirations of Bydgoszcz, necessity to construct the route S-5, and General Reporting and Electoral Meeting in October 2012.